Pendidikan PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE 3 PADA MATERI GOTONG ROYONG DI KELAS IV SEKOLAH DASAR - Ferdiantara, Diego; Atri Waldi; Reinita; Sahrun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the implementation of Pancasila Education in elementary schools, which is still dominated by conventional methods with limited media use, resulting in less interactive learning that does not accommodate students’ characteristics, who tend to be active and interested in technology-based media. This study aimed to develop an Articulate Storyline 3-based learning media on the topic of mutual cooperation for fourth-grade elementary students that is valid, practical, and effective. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included expert validators, teachers, and fourth-grade students from three elementary schools, totaling 75 students. The instruments used were validation sheets, practicality questionnaires, and learning outcome tests. The results showed that the developed media had a very high level of validity, with material validation at 97.1%, language validation at 90.6%, and media validation at 93%. The practicality results based on teacher responses were 95.83% at SDN 13 Batu Gadang, 100% at SD Semen Padang, and 95.83% at SDN 20 Indarung. Student responses were 91.30%, 93.67%, and 95% respectively. The effectiveness of the media was indicated by N-Gain scores of 0.797877847 at SDN 13 Batu Gadang, 0.847663139 at SD Semen Padang, and 0.80152381 at SDN 20 Indarung, all categorized as high. Therefore, the Articulate Storyline 3-based learning media is considered feasible for use in Pancasila Education on the topic of mutual cooperation in fourth-grade elementary schools